Early Post Endoscopic Retrograde Cholangiopancreatography (ERCP) Cholecystitis - Incidence, Risk Factors, Severity, and Surgical Implications — Case Series - Ravikiran SK; Nitin Rao AR; Lokesh LV; Avinash B; Manjunath Patil Kiran R; Satyaprakash BS (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Cholecystitis can be a serious complication following endoscopic retrograde cholangiopancreatography (ERCP). Though the concept of early post-ERCP cholecystitis (PEC) is well known, studies that analysed the predictors, occurrence and outcomes of early PEC are rare. This is an analysis of 11 cases developing severe early post-ERCP cholecystitis.